Developing A Model Of Receptivity To International Work - Abd Talib, Lilis Surienty; Ishak, Noormala; Omar, Azizah; Abdul Ghani, Rohayu (Universiti Sains Malaysia, 2011)
Receptivity to international work is conceptualised as individuals inclination or willingness to pursue international careers. The high number of Malaysian who went to work and stayed abroad instead of returning to Malaysia to work ("Growing", 2007; "Scheme", 2005) can cause problems to Malaysia's long term planning and knowledge transfer back into the country. It is pertinent to identify factors that relate early to Malaysian's developing an interest to international work and it is fundamental to question whether the early receptivity develops for those who have been abroad or anyone. This study aims to explain how people form career interests, make choices, and achieve educational and occupational ambitions. Specifically, personal agency and perceived environment in combination is said to explain the initial model of individual development of international career interest (Tharenou, 2003). It is proposed that motivational and family attachment factors would have interactive effects with personal agency and environmental factors to explain Malaysian receptivity to international work. Family attachment may actually reduce Malaysian receptivity to international work later in the employment tenure than immediately. In addition, Malaysian/Asian may conceptualise motivational and family attachment differently. Unlike most Western graduates who are educated locally, Malaysians has quite a number of its citizens being educated overseas. Therefore, the Malaysian sojourning experience would definitely be different from the Western model.